Directional Moving Target Indication: A Novel SAR Ambiguity Function for Traffic Monitoring. (15th March 2012) - Marques, Paulo
Abstract : This paper presents and evaluates a novel SAR ambiguity function for traffic monitoring. The novelty consists in introducing the capability to discriminate targets moving in a predefined direction of interest, reducing the contribution of traffic moving in undesired directions. Experimental results show that the modified SAR ambiguity function provides better results than the traditional methodology and may, therefore, be useful for civil traffic monitoring using single-channel synthetic aperture radar data.